Glucocorticoids Elevate Pseudomonas aeruginosa Binding to Airway Epithelium by Upregulating Syndecan-1 Expression - Liu, Dong; Zeng, Ying-Ying; Shi, Meng-Meng; Qu, Jie-Ming (Frontiers in Microbiology, 2021)
Glucocorticoids are commonly used for the treatment of asthma and chronic obstructive pulmonary disease (COPD). Inhaled corticosteroids were associated with a significantly increased risk of pneumonia. Syndecan-1 (SDC1) located in the cell membrane of airway epithelial cell is the crucial molecular mediating infections by P. aeruginosa (PA). In the present study, we found SDC1 expression was up regulated greatly and the adhesion of PA to human bronchial cell line (HBE) increased to 125% and 138% respectively after stimulation by dexamethasone or budesonide. The HBE cells knocking down SDC1 showed lower affinity to PA compared with control. CCAAT-enhancer-binding protein β (C/EBPβ) and its phosphorylated form participated in the regulation of glucocorticoid to SDC1 for interfering C/EBPβ or inhibiting phosphorylation of C/EBPβ by Licl and BIO, which are inhibitors of glycogen synthase kinase 3β (GSK-3β), could prevent glucocorticoids to up regulate SDC1 expression. Administrating glucocorticoids should be cautious in chronic lung disease for their property of increasing the expression of SDC1 and PA binding to airway epithelium.